Terapi Menulis Sebagai Media Muhasabah Untuk Menurunkan Tingkat Stres: Studi Eksperimental pada Mahasiswa UIN K.H. Abdurrahman Wahid Pekalongan - Himawanti, Izza (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Students in college are often have various internal and external stressors, including conflicts with friends, family, lovers, financial problems, difficulty managing time, academic assignments, health, body image, transportation, etc. This stressor is the cause of the high level of stress in students. The purpose of this study was to determine the effect of writing therapy as a media of muhasabah in reducing stress levels in college students. Writing therapy is carried out for five consecutive days, using muhasabah indicators and psychological writing therapy techniques. This research uses pre-experimental research method, with pre and post-test one group design. The dependent variable in this research is the level of stress on students, while the independent variable is the treatment given, namely writing therapy as a muhasabah. The research subjects totaled 88 students, with the criteria of active students at UIN KH. Abdurrahman Wahid, had experienced online and offline learning and was willing to pro-actively participate in the entire series of therapies, subjects were selected by cluster random sampling. Data collection techniques using the stress scale and hypothesis testing using the t-test. based on the results of the parametric statistical test t-test as obtained t-test significance of 0.001 which is less than 0.05, this indicates that writing therapy as a of muhasabah has a positive effect on reducing student in college stress levels.